C. S. Lewis and the crisis of a Christian - Cootsona, Gregory S. (Louisville, Kentucky : Westminster John Knox Press, 2014)
"C.S. Lewis has long been recognized as a beloved author of children's literature and an apologist for Christian belief to a skeptical modern world. In this new volume, Gregory S. Cootsona shows us how Lewis can also serve as a guide to the ups and downs of the Christian journey. Like many of us, Lewis suffered from a variety of crises of faith and personal experience. Like us, he came to faith in a world that no longer respects Christian commitment or offers much room for belief in God. Like us, he felt the absence of God when those closest to him died. Like us, he wrestled with doubt, wondering if God is real, or simply the projection of his own wishes onto the screen of the universe. Like us, he knew the kinds of temptations he described with such poignancy and humor in The Screwtape Letters.By examining these and the other crises of C.S. Lewis's life, Cootsona shows us how Lewis found God in each one, and how he shared those discoveries with us in his writing. All those wishing to deepen and enrich their own spiritual journey will find much guidance and wisdom in these pages"--
Introducing C. S. Lewis -- The crises of atheism. The crisis of materialism ; The crisis of meaninglessness ; The crisis of Anomie -- The crises of Christian faith. Jesus and the crisis of other myths ; The crisis of the Bible -- The crises of human life. The crisis of feeling ; The crisis of suffering ; The crisis of death.
Includes bibliographical references.
Keywords: Lewis, C. S. -- 1898-1963.; Anglican converts -- England -- Biography; Christian biography -- England